VOICES OF GYPSY WOMEN FROM NEUQUEN: AN ETHNOGRAPHIC APPROACH WITH A GENDER PRESPECTIVE (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2026)
This article explores the construction of female identity within a Roma (Gitano) family in the city of Neuquén, using an ethnographic approach and a gender perspective. Through fieldwork, in-depth interviews, and bibliographic review, the study analyzes the central role of women in cultural reproduction, life-cycle rituals, and family organization. It also examines the tensions between traditional mandates and transformations arising from interactions with mainstream society. The findings highlight how Roma women, while embedded in patriarchal norms, actively engage in processes of resignification that challenge stigmatizing discourses and open new paths for agency.
Keywords: Roma community, female identity, gender roles, ethnography, Neuquén, tradition and change.